Overcoming the theoretical duality on social enterprise formation. Issue 3 (8th July 2020) - Nascimento, Leandro da Silva; Salazar, Viviane Santos
Abstract : Purpose: Nowadays, creation and discovery theories are the two main theoretical approaches supporting the studies on the emergence of enterprises and some scholars analyze these theories in isolation. In addition, studies that investigate the emergence of social enterprises based on these theories together are scarce. This paper aims to analyze if and how discovery and creation theories can coexist in the formation process of social enterprises. Design/methodology/approach: A multi-case study based on semi-structured interviews with the founders of eight Brazilian social enterprises was conducted. Findings: From the results, it is identified that there is a continuous process between discoveries and creations that lead to the maturation of the initial idea and, consequently, to the formation of a social enterprise. Therefore, a continuous process model between discovery and creation of opportunities in the formation of a social enterprise (i.e. a mixed theoretical approach) is proposed, going beyond a theoretical duality between creation or discovery. Originality/value: This study helps to overcome limitations inherent in both discovery and creation theories, proposing a mixed theoretical approach. This new theoretical approach praises the existence of new paths to understand the emergence of social enterprises, by overcoming the theoretical duality between creation or discovery of opportunities, i.e. a new understanding of an integrating process rather than a dichotomous one.